The Effect of Capital Adequacy, Lending Interest Rates, Credit Risk and Third Party Funds on Return on Asset (ROA) (Empirical Study on Conventional Banking Companies Listed on the Indonesia Exchange in 2019-2023) - Munzir, Antoni; Mareta, Sigit; Khaled, Januar; Suryadi, Edy (DINASTI RESEARCH, 2025)
This study is to determine the effect of third party fund growth, credit interest rates, credit risk, capital adequacy and economic conditions on profitability in the banking industry on the Indonesian stock exchange. The population in this study were banking companies on the Indonesian Stock Exchange for the period 2019-2023. The sampling technique used was purposive sampling, and 25 banking company. The data collection method used in this study was non-participant observation. The data analysis technique was carried out using multiple linear regression analysis with the help of the SPSS 27.0 application. Findings: The results of this study indicate that Capital Adequacy has a positive and insignificant effect on Return on Assets (ROA). Interest Rate Level has a positive and significant effect on Return on Assets (ROA). Credit Risk has a positive and significant effect on Return on Assets (ROA). Third Party Funds have a positive and insignificant effect on Return on Assets (ROA). The results of this study have implications for the Community who will invest, giving them a better basis in making savings and investment decisions. The author explains the importance of the Influence of Capital Adequacy, Credit Interest Rates, Credit Risk and third party funds on Return on Assets (ROA).